1995
DOI: 10.1128/jb.177.10.2918-2922.1995
|View full text |Cite
|
Sign up to set email alerts
|

The rpoE gene of Escherichia coli, which encodes sigma E, is essential for bacterial growth at high temperature

Abstract: In vitro transcription analysis has shown that only RNA polymerase containing an alternative sigma subunit, E , activates transcription from one of the rpoH promoters and the htrA promoter. The location of the rpoE gene encoding E on the Escherichia coli chromosome has recently been established, but no rpoE mutant has yet become available for phenotypic testing. We cloned the rpoE gene from the -ordered clones of the E. coli genome and confirmed that the reconstituted RNA polymerase containing the gene product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 27 publications
1
84
1
1
Order By: Relevance
“…In a subsequent study, Martin et al (1994) showed that the ¹35 and ¹10 regions of promoters transcribed by AlgU shared considerable similarity with the known promoter consensus sequence for E , the second heat-shock sigma factor identified at the biochemical level in Escherichia coli (Erickson and Gross, 1989). These and subsequent sequence analyses permitted the identification of E. coli and Salmonella typhimurium rpoE genes based on striking homologies of their gene products with AlgU (Hiratsu et al, 1995;Martin et al, 1994;Raina et al, 1995;Rouviè re et al, 1995). These observations and additional analyses have uncovered the existence of a broader family of novel alternative sigma factors termed ECF (Lonetto et al, 1994) or E -like factors .…”
Section: Introductionmentioning
confidence: 98%
“…In a subsequent study, Martin et al (1994) showed that the ¹35 and ¹10 regions of promoters transcribed by AlgU shared considerable similarity with the known promoter consensus sequence for E , the second heat-shock sigma factor identified at the biochemical level in Escherichia coli (Erickson and Gross, 1989). These and subsequent sequence analyses permitted the identification of E. coli and Salmonella typhimurium rpoE genes based on striking homologies of their gene products with AlgU (Hiratsu et al, 1995;Martin et al, 1994;Raina et al, 1995;Rouviè re et al, 1995). These observations and additional analyses have uncovered the existence of a broader family of novel alternative sigma factors termed ECF (Lonetto et al, 1994) or E -like factors .…”
Section: Introductionmentioning
confidence: 98%
“…E. coli MC4100 lF [htrA-lacZ] (Hiratsu et al, 1995) (Kadokura et al, 1994) is a pBR322-derived plasmid that expresses phoA under its own promoter. Plasmid pRS414 and pRS415 (Simons et al, 1987) are generous gifts of R. W. Simons, Department of Microbiology, University of California, Los Angeles, USA.…”
Section: Methodsmentioning
confidence: 99%
“…The level of PhoA synthesis increased in keeping with the IPTG concentration, confirming the regulated expression of phoA from the trc promoter. To examine the level of degP transcription in these cells, we used a htrA-lacZ fusion gene (Hiratsu et al, 1995), in which degP promoter is immediately followed by a lacZ gene lacking its own promoter. As Fig.…”
Section: Transcription Of Degp Is Induced Upon Overexpression Of Phoamentioning
confidence: 99%
“…s E , first identified as a transcription factor for the rpoH gene, which encodes a main heat-shock s factor (Erickson & Gross, 1989;Wang & Kaguni, 1989), is involved in the expression of several E. coli genes (De Las Peñas et al, 1997a;Rouviëre et al, 1995) whose products deal with unfolded periplasmic or membrane proteins caused by heat shock or environmental stresses Raina et al, 1995;Rouviëre et al, 1995). s E has been demonstrated to be an essential sigma factor in the organism at both high and low temperatures (De Las Peñas et al, 1997b;Hiratsu et al, 1995;Lipinska et al, 1989). The accumulation of unfolded extracytoplasmic proteins triggers intracellular active s E molecules (Mecsas et al, 1993) via a unique mechanism of s E modulation, in which RseA, RseB and RseC, encoded by the rpoE-rseABC operon, may be involved (De Las Peñas et al, 1997a;.…”
Section: Introductionmentioning
confidence: 99%